Study of cardiovascular eligibility for hormonal contraception in women in Porto-Novo - Arnaud Sonou; Richard Aniglé; Corine Houehanou; Armand Wanvoègbè; Mathieu Ogoudjobi; Dèdonougbo Martin Houénassi (Archives of Clinical Hypertension - Peertechz Publications, 2020)
Introduction: The aim of this study was to determine the cardiovascular eligibility rate for hormonal contraception among women in Porto-Novo, with reference to the criteria defined by the World Health Organization (WHO). Materials and methods: A descriptive cross-sectional study was conducted in 2016 over a period of 4 months at the headquarters of the Beninese Association for the Family Promotion (ABPF) in Porto-Novo, Benin. It exhaustively included all women who came to renew their hormonal contraception. The verification procedure useful for the renewal of the contraceptive used included the search for cardiovascular risk factors (high blood pressure, hyperglycemia, obesity, smoking). Based on the eligibility criteria defined by WHO for each type of contraceptive and on the presence or absence of the risk factors sought, each woman surveyed was declared eligible or ineligible for continuation of the contraceptive in progress. Results: Three hundred and seventy-five women were included in this work. The average age was 35.3±8.2 years. A pure progestin hormone was used in 97.9% (N= 367) of cases and a combined estrogen-progestin hormone was used in 2.1% (N= 8) of cases. High blood pressure, high fasting blood glucose, obesity and smoking in the previous 12 months were found in 24% (N= 90), 1.5% (N= 6), 23.2% (N= 87) and 0.3% (N= 1) of the participants, respectively. Ninety percent of the women surveyed (N= 336) were eligible for current contraceptive use, which prevented detrimental renewal for 10% (N= 39) of them. Conclusion: This study showed that one in 10 women used detrimental hormonal contraception. A strong collaboration between the actors in the chain, i.e. the woman herself, the family planning agent and the general practitioner or specialist is an important objective that would ensure the effectiveness of family planning strategies while combating preventable cardiovascular disease.